2022
DOI: 10.3390/ijerph19148793
|View full text |Cite
|
Sign up to set email alerts
|

Recovering from Intimate Partner Violence through Strengths and Empowerment (RISE): Initial Evaluation of the Clinical Effects of RISE Administered in Routine Care in the US Veterans Health Administration

Abstract: Intimate partner violence (IPV) is a common concern among military Veterans that negatively impacts health. The United States’ Veterans Health Administration (VHA) has launched a national IPV Assistance Program (IPVAP) to provide comprehensive services to Veterans, their families and caregivers, and VHA employees who use or experience IPV. Grounded in a holistic, Veteran-centered psychosocial rehabilitation framework that guides all facets of the program, the IPVAP initiated the pilot implementation of a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…To improve the health and safety of MSM who disclose they are already experiencing IPV, recovering from IPV through strengths and empowerment (RISE) is another promising transdiagnostic intervention that utilizes motivational interviewing delivered over a series of sessions (Iverson et al, 2022). RISE is clinician delivered and the content, which was designed to be gender neutral, has demonstrated acceptability among men (Iverson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the health and safety of MSM who disclose they are already experiencing IPV, recovering from IPV through strengths and empowerment (RISE) is another promising transdiagnostic intervention that utilizes motivational interviewing delivered over a series of sessions (Iverson et al, 2022). RISE is clinician delivered and the content, which was designed to be gender neutral, has demonstrated acceptability among men (Iverson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To improve the health and safety of MSM who disclose they are already experiencing IPV, recovering from IPV through strengths and empowerment (RISE) is another promising transdiagnostic intervention that utilizes motivational interviewing delivered over a series of sessions (Iverson et al, 2022). RISE is clinician delivered and the content, which was designed to be gender neutral, has demonstrated acceptability among men (Iverson et al, 2022). In addition to universal screening, education, and empowerment, supplemental targeted interventions to support reduction of IPV that are tailored to risk factors among the most affected MSM populations (i.e., those who engage in substance use, are younger, experience depression, are economically insecure, and/or experience multiple minority stressors) are needed.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 73 , 74 IF’s utility in increasing the uptake of services among screened women is important because VHA offers advocacy, evidence-based psychotherapies, 27 and IPV-specific interventions that can improve psychosocial health. 70 , 75 …”
Section: Discussionmentioning
confidence: 99%
“…Identification and effective treatment of mental health symptoms may strengthen efforts to prevent and reduce IPV, but relatively little research to date has specifically focused on this topic [72]. There is evidence that some psychosocial counseling and advocacy-based interventions for women who experience IPV, including samples of veterans, lead to improvements in mental health and possible reductions in IPV experience [73][74][75][76]. In addition, Iverson et al [14] found that women interpersonal trauma survivors who experienced substantial reductions in PTSD and depression symptoms during cognitive behavioral therapy for PTSD were less likely to report experiencing IPV at a 6-month follow-up compared to women who did not experience similar reductions in these mental health symptoms, adjusting for baseline experiences of IPV.…”
Section: Discussionmentioning
confidence: 99%